LINGUOCULTURAL ANALYSIS OF THE CONCEPT OF “INDIOS” IN THE LINGUISTIC WORLDVIEW OF SPANIARDS DURING THE GOLDEN AGE - Operailo, Serhii (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2025)
The article examines the meaning of the concept of "indios" in the linguistic worldview of Spaniards during the Golden Age. The research is based on historical sources from the 16th century. It analyzes the linguistic means that verbalize the cognitive content of the concept of "indios" through linguistic expression. The analysis of examples reveals the ambiguity of the perception of the concept of “indios” in the Spanish-speaking society of that time, allowing for the identification of three differentiated models of world perception among 16th-century Spaniards. The findings of the study open new perspectives for further research on the linguistic worldview of Spaniards during the Golden Age, which reflects the origins of certain elements of the nation’s modern consciousness.______________References:• Cortés, H. (1979). Cartas de relación de la conquista de México. Madrid: Espasa-Calpe. Retrieved from https://archive.org/details/isbn_8423905470/mode/2up• Landa, D. De. (2002). Relación de las cosas de Yucatán. Dastin Export S.L. Retrieved from https://archive.org/details/relaciondelascos0000dieg• Sepulveda, J. G. De. (2016). Democrates Segundo, O De Las Justas Causas. Clásicos de Historia. Retrieved from https://archive.org/details/sepulveda-juan-gines-de.-democrates-segundo-o-de-las-justas-causas-2016/mode/2up• Vilchynska, T. P. (2009). Osnovni pidkhody do vyznachennia kontseptu v linhvistychnii paradyhmi. Naukovi zapysky Ternopilskoho natsionalnoho pedahohichnoho universytetu, (2), 26–33.• Poliuzhyn, M. M. (2009). Typolohiia y analiz kontseptiv. Inozemna filolohiia, (121), 80–89.• Popova, N. M. (2018). Evoliutsiia natsionalno-markovanykh kontseptiv u movnii kartyni svitu Ispanii (XVI-XX stolittya) [Avtoref. dys. ... d-ra filol. nauk: 10.02.05]. Kyiv: Kyivskyi natsionalnyi universytet im. Tarasa Shevchenka.
Keywords: linguocultural analysis, semantic-cognitive analysis, concept, Spanish linguistic worldview, Spain during the Golden Age